PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF METODE GROUP INVESTIGATION (GI) UNTUK MENINGKATKAN KEMAMPUAN SISWA DALAM MENYELESAIKAN SOAL CERITA MATEMATIKA - Kamsiyati, Siti; marwiyanto, Marwiyanto; Rintayanti, Peduk; Samsiyah, Siti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2014)
Abstract: The purpose of this research is to improve the students capability in finishing the story problem of comparison topic in sixth grade SD Negeri Kleco 02 Laweyan Surakarta by using Group Investigation (GI) method. Variable as the target of the change in this research in improving the students capability in doing comparison story problem. while the action variable used is Group Investigation (GI). The sample of this research is all students (36 students) of sixth grade of SD Negeri Kleco 02 Laweyan Surakarta. Data of capability improvement of story problem finishing is collected techniques of this research are observation. test and documentation. The data was analyzed by using an interactive analysis model with three components; data reduction. Data presentation and conclusion or verification. Conclusions can be drawn based on the result of the research; Mathematic learning through Group Investigation (GI) method can improve the students capability to finish the story problem of sixth grade students of SD Negeri Kleco 02 Laweyan Surakarta. It is proven on the condition before the action where the averaged grade was 64.3 with the percentage of classical completeness is 56%. Cycle I indicated the averaged grade of class is 80.8 with the classical completeness percentage of 72% and cycle II it increased become 86.0 with classical completeness percentage of 91%. Therefore a recommendation can be addressed that mathematic learning by using Group Investigation (GI) method can improve the students capability to finish the story problem of sixth grade SD Negeri Kleco 02 Laweyan in 2010/2011 academic year. Abstrak: Tujuan penelitian ini adalah untuk meningkatkan kemampuan siswa dalam menyelesaikan soal cerita dengan membandingkat topik di kelas 6 SD Negeri Kleco 02 laweyan Surakarta dengan menggunakan metode Group Investigation (GI). variabel perubahan dalam penelitian ini dalam meningkatkan kemampuan siswa dalam menyelesaikan masalah cerita. Variabel kerja yang digunakan adalah Group Investigation (GI). Sampel dalam penelitian ini adalah 36 siswa pada kelas 6 SD Negeri Kleco 02 Laweyan Surakarta. Teknik pengumbulan data adalah observasi, ujian, dan dokumentasi. Data dianalisis dengan menggunakan model analisis interaktifdengan 3 komponen; pengurangan data. Presentasi data dan kesimpulan atau verifikasi. Kesimpulan dari hasil penelitian ini: pembelajaran matematika melalui Group Investigation bisa meningkatkan kemampuan siswa dalam menyelesaikan soal cerita. Hal ini membuktikan pada kondisi sebelum diberikannya perlakuan dimana nilai rata-rata adalah 64,3 dengan persentase penyelesaian klasik adalah 56%. Siklus I mengindikasikan nilai rata-rata kelas adalah 80,8 dengan persentase penyelesaian klasik sebesar 72%, dan siklus II meningkat menjadi 86,0 dengan persentase penyelesaian klasik sebesar 91%. Oleh karena itu, pembelajaran matematika dengan menggunakan metode Group Investigation (GI) bisa meningkatkan kemampuan siswa dalam menyelesaikan soal cerita pada kelas 06 SD Negeri Kleco 02 Laweyan pada tahun 2010/2011.